Coal gasification slag unfired ceramsite filter material as well as preparation method and application thereof

By using raw materials such as coal gasification slag, the problem of easy blockage of traditional filter materials and high waste treatment costs is solved, efficient and environmentally friendly oil field sewage treatment is achieved, and a harmless treatment method for waste filter materials is proposed, which has improved the value of resource utilization.

CN119656718APending Publication Date: 2025-03-21CHINA UNIV OF MINING & TECH

Patent Information

Application Number
CN202411837267.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the existing oilfield sewage treatment, traditional filter materials are easily blocked due to the adhesion of oil and impurities, the cleaning process is cumbersome, and the waste filter materials are treated at high cost and the treatment process is complicated. At the same time, traditional non-burning ceramic filters will release a large amount of carbon dioxide during the production process.

Method used

The raw materials such as gasification slag, metakaolin, solid sodium silicate, expanded perlite, hydrogen peroxide and cetyl trimethyl ammonium bromide were prepared. By adjusting the raw material ratio and curing conditions, ceramic granule filter materials with high porosity, high strength and low water absorption were prepared, and a method of high-temperature roasting treatment of failed filter materials was proposed to prepare concrete test blocks.

Benefits of technology

The reusable use of ceratops filter materials is achieved, the preparation process is green and environmentally friendly, and the subsequent disposal cost is low. The ceratops filter materials have excellent performance in oil field sewage treatment, and the treatment effect is comparable to traditional clay ceratops filter materials. The waste filter materials can be harmlessly treated and reused.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119656718A_ABST
    Figure CN119656718A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of water treatment materials, and particularly relates to a coal gasification slag unfired ceramsite filter material as well as a preparation method and application thereof. The coal gasification slag thermal insulation material comprises the following raw materials in parts by weight: 67.5-95 parts of coal gasification slag, 5-15 parts of active powder, 0-20 parts of metakaolin, 2-8 parts of expanded perlite, 0.1-0.5 part of a foam stabilizer and 1-3 parts of a foaming agent. The unfired ceramsite filter material has the advantages of being reusable, green and environment-friendly in preparation process, low in follow-up treatment cost, capable of being reused after failure and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of water treatment materials, and in particular relates to a coal gasification slag unburned ceramsite filter material and a preparation method and application thereof. Background Art

[0002] Oilfield wastewater is a complex wastewater separated during the dehydration of crude oil. It has the characteristics of high oil content, high emulsification degree, and high content of suspended solids. Direct discharge without treatment will pollute the soil and water sources, while reinjection will cause formation blockage and reduce formation permeability. In the current deep treatment of oilfield wastewater, traditional filter materials such as quartz sand, walnut shells and anthracite are often blocked due to the adhesion of oil and impurities, resulting in the ineffectiveness of the filter material, and the cleaning process is cumbersome, which further increases the treatment cost. In addition, the treatment cost of waste filter materials such as walnut shells that fail to backwash is high, and the treatment process is complicated.

[0003] Ceramic particle filter material has the characteristics of high strength, good chemical stability, large specific surface area and high porosity. It can effectively remove emulsified oil and fine suspended matter in water. It is a new type of water treatment material. According to the different preparation methods, ceramsite filter materials are divided into sintered ceramsite filter materials and unfired ceramsite filter materials. The preparation process of traditional sintered ceramsite filter materials is not only energy-intensive and costly, but also produces harmful gases. Traditional unfired ceramsite filter materials use clay and shale as the ceramic matrix and cement as the binder. Clay and shale are non-renewable resources, and a large amount of carbon dioxide is also released during the cement production process.

[0004] Therefore, there is an urgent need for a coal gasification slag unburned ceramsite filter material and a preparation method and application to solve the above problems. Summary of the invention

[0005] In order to overcome the defects in the above-mentioned prior art, the present invention provides a coal gasification slag unfired ceramsite filter material and a preparation method and application thereof. The unfired ceramsite filter material of the present invention has the advantages of being reusable, having a green and environmentally friendly preparation process, having low subsequent disposal costs, and being reusable after failure.

[0006] To achieve one of the above purposes, the present invention adopts the following technical solution:

[0007] A coal gasification slag unburned ceramsite filter material, comprising the following raw materials in parts by weight:

[0008] 67.5-95 parts of coal gasification slag, 5-15 parts of active powder, 0-20 parts of metakaolin, 2-8 parts of expanded perlite, 0.1-0.5 parts of foam stabilizer, and 1-3 parts of foaming agent.

[0009] Preferably, the coal gasification slag comprises 95-98 wt % of ash, the particle size of the coal gasification slag is 0-0.25 mm; the particle size of the metakaolin is 0-0.25 mm; and the particle size of the expanded perlite is 0-0.074 mm.

[0010] Preferably, the active powder is composed of solid sodium silicate (Na2SiO3) with a purity of 83.9%; the foam stabilizer is cetyltrimethylammonium bromide (CTAB) with analytical grade; and the foaming agent is hydrogen peroxide (H2O2) with a concentration of 30%.

[0011] To achieve the second purpose above, the present invention provides a method for preparing a coal gasification slag unburned ceramsite filter material, comprising the following steps:

[0012] S1. Mixing: weighing raw materials in parts by mass and mixing them evenly to obtain a mixture;

[0013] S2, granulation: adding water and foaming agent to the mixture, mixing and placing in a granulator for granulation to obtain ceramsite raw material;

[0014] S3, curing: subjecting the ceramsite raw material to aging treatment, steam curing and natural drying in sequence to obtain ceramsite filter material.

[0015] Preferably, in step S1, the raw materials are dried at 105° C. before mixing; and a planetary ball mill is used to operate at a rotation speed of 400 rpm for 5 minutes during mixing.

[0016] The raw materials are dried before entering the ball mill for mixing. On the one hand, this facilitates more uniform mixing of the raw materials. On the other hand, it prevents the raw materials from containing moisture, which may cause the active powder to react with coal gasification slag, kaolin, etc. in advance.

[0017] Preferably, in step S2, the granulator is a strong mixing granulator, the rotor speed of the granulator is 1400rpm-1600rpm, the feed plate speed of the granulator is 30rpm; and the particle size of the ceramsite raw material is 2-3mm.

[0018] Preferably, in step S3, the aging temperature is 25±2°C; the aging time is 12-18h; the curing temperature is 40-80°C, the curing humidity is 95%, and the curing time is 6-15h; the natural drying temperature is 25±2°C, and the drying time is 12-18h.

[0019] To achieve the third purpose above, the present invention provides an application of coal gasification slag unburned ceramsite filter material, and the ceramsite filter material is applied to the deep treatment of oilfield wastewater.

[0020] The specific steps are as follows:

[0021] The ceramsite filter material is loaded into the filter device, which is set up in a top-down flow manner and uses a metal mesh as a supporting layer; the oilfield wastewater enters the filter device from the top and is discharged from the bottom of the filter device after filtration.

[0022] After deep treatment of oilfield wastewater, the ceramsite filter material can be reused. When it is used next time, the ceramsite filter material is backwashed at a backwashing flow rate of 8-12m / h.

[0023] Preferably, the diameter of the filter device is 30 mm and the height is 1200 mm; the oil content of the oilfield wastewater is 15-50 mg / L, the solid suspended matter concentration of the oilfield wastewater is 15-20 mg / L; and the filtration speed is 5 m / h.

[0024] Preferably, the concrete test blocks are prepared using spent ceramsite filter materials after deep treatment of oilfield wastewater.

[0025] The specific steps for preparing concrete test blocks are as follows:

[0026] The ceramsite filter material was calcined at a high temperature of 350°C-500°C for 1 hour, and then the calcined ceramsite filter material was mixed with cement to prepare a concrete test block, and standard curing was performed for 28 days to obtain a concrete test block.

[0027] Preferably, the mass ratio of cement: ceramsite filter material: water in the concrete test block is 1:4:0.5; the curing temperature is 20±2°C and the humidity is 95±2°C; and the size of the concrete test block is 15cm×15cm×15cm.

[0028] The advantages of the present invention are:

[0029] (1) The present invention uses coal gasification slag and metakaolin as ceramsite matrix materials, solid sodium silicate as an alkali activator, expanded perlite as a pore-forming material, hydrogen peroxide as a foaming agent, and hexadecyltrimethylammonium bromide as a foam stabilizer to successfully prepare a non-fired ceramsite filter material with high porosity, high strength and low water absorption. The coal gasification slag and metakaolin undergo processes such as dissolution, depolymerization, reorganization and hardening in an alkaline environment. By adjusting the raw material ratio and curing conditions, the reaction process is promoted to provide excellent strength for the ceramsite filter material. At the same time, hydrogen peroxide decomposes to produce gas, and the porous structure of the expanded perlite adds abundant pores to the ceramsite filter material. The present invention not only provides a new idea for the resource utilization of coal gasification slag, but also has green and environmentally friendly advantages such as low cost, low energy consumption, and low carbon emissions compared with sintered ceramsite filter materials and traditional non-fired ceramsite filter materials.

[0030] (2) Compared with traditional filter materials (such as walnut shells and quartz sand), the ceramsite filter material of the present invention has the characteristics of adjustable particle size, good sphericity, not easy to be blocked or compacted, long service life, and easy backwashing and regeneration. When applied to the deep treatment of oilfield wastewater, it can effectively remove emulsified oil and fine suspended matter, and then realize the recycling and regeneration of the filter material through backwashing, which can further improve the efficiency and economy of wastewater treatment.

[0031] (3) For the ceramsite filter material that fails to backwash, the present invention proposes to remove the oil components in the failed filter material by high-temperature roasting, and add the roasted ceramsite filter material as aggregate into cement to prepare concrete test blocks, thereby achieving harmless treatment and reuse of the waste filter material, which not only improves the potential performance of concrete materials (such as impact resistance and thermal insulation), but also provides a more environmentally friendly and economical solution for the treatment of waste filter materials. Compared with traditional filter materials such as walnut shell filter material, the ceramsite filter material prepared by the present invention has higher reuse value, superior physical and chemical stability, potential for improving the performance of building materials, and lower processing cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The present invention is a flow chart of the preparation and application of the coal gasification slag unfired ceramsite filter material. DETAILED DESCRIPTION

[0033] Example 1

[0034] A method for preparing coal gasification slag unburned ceramsite filter material comprises the following steps:

[0035] S1. Mixing: by weight, coal gasification slag: sodium silicate = 87.5%: 12.5%, using a planetary ball mill at a speed of 400 rpm for 5 minutes to obtain a mixed material;

[0036] S2, granulation: adding 18% deionized water by weight to the mixture, granulating with a strong mixing granulator, the rotor speed is 1500rpm, the feed plate speed is 30rpm, the ceramsite raw material particle size range is 2-3mm, and the ceramsite raw material is obtained;

[0037] S3, curing: the raw material is subjected to aging treatment (temperature of 25° C., time of 12 h) - steam curing (temperature of 60° C., humidity of 95%, time of 12 h) - natural drying (temperature of 25° C., time of 12 h) to obtain ceramsite filter material 1.

[0038] Example 2

[0039] A method for preparing coal gasification slag unburned ceramsite filter material comprises the following steps:

[0040] S1. Mixing: by weight, coal gasification slag: sodium silicate: metakaolin = 95%:5%, using a planetary ball mill at a speed of 400 rpm for 5 minutes to obtain a mixed material;

[0041] S2, granulation: adding 18% deionized water by weight to the mixture, granulating with a strong mixing granulator, the rotor speed is 1500rpm, the feed plate speed is 30rpm, the ceramsite raw material particle size range is 2-3mm, and the ceramsite raw material is obtained;

[0042] S3, curing: the raw material is subjected to aging treatment (temperature of 25° C., time of 12 h) - steam curing (temperature of 60° C., humidity of 95%, time of 12 h) - natural drying (temperature of 25° C., time of 12 h) to obtain ceramsite filter material 2.

[0043] Example 3

[0044] A method for preparing coal gasification slag unburned ceramsite filter material comprises the following steps:

[0045] S1. Mixing: by weight, coal gasification slag: sodium silicate: metakaolin = 67.5%: 12.5%: 20%, using a planetary ball mill at a speed of 400 rpm for 5 minutes to obtain a mixed material;

[0046] S2, granulation: adding 18% deionized water by weight to the mixture, granulating with a strong mixing granulator, the rotor speed is 1500rpm, the feed plate speed is 30rpm, the ceramsite raw material particle size range is 2-3mm, and the ceramsite raw material is obtained;

[0047] S3, curing: subject the raw material to aging treatment (temperature of 25° C., time of 12 h) - steam curing (temperature of 60° C., humidity of 95%, time of 12 h) - natural drying (temperature of 25° C., time of 12 h) to obtain ceramsite filter material 3.

[0048] Example 4

[0049] A method for preparing coal gasification slag unburned ceramsite filter material comprises the following steps:

[0050] S1. Mixing: by weight, coal gasification slag: sodium silicate: metakaolin = 67.5%: 12.5%: 20%, and 8% expanded perlite is added additionally, and a planetary ball mill is used to operate at a speed of 400 rpm for 5 minutes to obtain a mixed material;

[0051] S2. Granulation: Add 18% deionized water by weight to the mixture, use a strong mixing granulator to granulate, the rotor speed is 1500rpm, the feed plate speed is 30rpm, and the ceramsite raw material particle size range is 2-3mm to obtain ceramsite raw material;

[0052] S3, curing: subject the raw material to aging treatment (temperature of 25° C., time of 12 h) - steam curing (temperature of 60° C., humidity of 95%, time of 12 h) - natural drying (temperature of 25° C., time of 12 h) to obtain ceramsite filter material 4.

[0053] Example 5

[0054] A method for preparing coal gasification slag unburned ceramsite filter material comprises the following steps:

[0055] S1. Mixing: by weight, coal gasification slag: sodium silicate: metakaolin = 67.5%: 12.5%: 20%, additionally add 8% expanded perlite and 0.1% CTAB, use a planetary ball mill to run at a speed of 400 rpm for 5 minutes to obtain a mixture;

[0056] S2, granulation: by weight, add 18% deionized water and 1% H2O2 to the mixture, use a strong mixing granulator to granulate, the rotor speed is 1500rpm, the feed plate speed is 30rpm, and the ceramsite raw material particle size range is 2-3mm to obtain ceramsite raw material;

[0057] S3, curing: subject the raw material to aging treatment (temperature of 25±2°C, time of 12-18h) - steam curing (temperature of 60°C, humidity of 95%, time of 12h) - natural drying (temperature of 25±2°C, time of 12-18h) to obtain ceramsite filter material 5.

[0058] Example 6

[0059] A method for preparing coal gasification slag unburned ceramsite filter material comprises the following steps:

[0060] S1. Mixing: by weight, coal gasification slag: sodium silicate: metakaolin = 67.5%: 12.5%: 20%, additionally adding 8% expanded perlite and 0.3% CTAB, using a planetary ball mill to run at a speed of 400 rpm for 5 minutes to obtain a mixture;

[0061] S2, granulation: by weight, add 18% deionized water and 2% H2O2 to the mixture, use a strong mixing granulator to granulate, the rotor speed is 1500rpm, the feed plate speed is 30rpm, and the ceramsite raw material particle size range is 2-3mm to obtain ceramsite raw material;

[0062] S3, curing: the raw material is subjected to aging treatment (temperature of 25±2°C, time of 12-18h) - steam curing (temperature of 60°C, humidity of 95%, time of 12h) - natural drying (temperature of 25±2°C, time of 12-18h) to obtain ceramsite filter material 6.

[0063] Example 7

[0064] A method for preparing coal gasification slag unburned ceramsite filter material comprises the following steps:

[0065] S1. Mixing: by weight, coal gasification slag: sodium silicate: metakaolin = 67.5%: 12.5%: 20%, additionally add 8% expanded perlite and 0.5% CTAB, use a planetary ball mill to run at a speed of 400 rpm for 5 minutes to obtain a mixture;

[0066] S2, granulation: by weight, add 18% deionized water and 3% H2O2 to the mixture, use a strong mixing granulator to granulate, the rotor speed is 1500rpm, the feed plate speed is 30rpm, and the ceramsite raw material particle size range is 2-3mm to obtain ceramsite raw material;

[0067] S3, curing: the raw material is subjected to aging treatment (temperature of 25±2°C, time of 12-18h) - steam curing (temperature of 60°C, humidity of 95%, time of 12h) - natural drying (temperature of 25±2°C, time of 12-18h) to obtain ceramsite filter material 7.

[0068] Example 8

[0069] An application of coal gasification slag unburned ceramsite filter material, ceramsite filter material 1 to ceramsite filter material 7 prepared in Examples 1-7 are used for deep treatment of oilfield wastewater, the oil content of the wastewater is 20.38 mg / L, and the concentration of suspended solids is 18.52 mg / L, and the specific steps are as follows:

[0070] The ceramsite filter material with a particle size of 2-3mm is filled in a filter device with a diameter of 30mm and a height of 1200mm, and a metal mesh is used as a supporting layer; when filtering oilfield wastewater, the water flow direction is from top to bottom, the filtration speed is 5m / h, and the filtered water samples are taken every 1h to test the oil content.

[0071] Example 9

[0072] The gasified slag unburned ceramsite filter material which was invalid after deep treatment of oilfield sewage in Example 8 was calcined at 400°C for 1h to remove the oil component in the filter material, and the calcined ceramsite filter material was added to cement as aggregate. A 15cm×15cm×15cm concrete test block was prepared according to the ratio of cement (model P.O32.5): aggregate: water = 1:4:0.5, and after standard curing (temperature 20±2°C, humidity 95±2°C) for 28 days, a concrete test block was obtained.

[0073] Comparative Example 1

[0074] The specific preparation method of traditional clay ceramsite filter material is as follows:

[0075] S1. Mixing: by weight, clay: cement = 60%: 40%, additionally add 8% expanded perlite and 0.1% CTAB, use a planetary ball mill to operate at a speed of 400 rpm for 5 minutes to obtain a mixture; step S2 and step S3 are the same as the steps in Example 3.

[0076] Comparative Example 2

[0077] Application of traditional clay ceramsite: The clay ceramsite filter material prepared in Comparative Example 1 is used to deeply treat oilfield wastewater according to the application method of the ceramsite filter material in Example 8.

[0078] Comparative Example 3

[0079] The conventional clay ceramsite was used to prepare concrete test blocks after the backwashing failed. The clay ceramsite that failed after deep treatment of oilfield wastewater in Comparative Example 2 was used to prepare concrete test blocks according to the preparation method of Example 9.

[0080] Comparative Example 4

[0081] Application of walnut shell filter material: The commercially available walnut shell filter material is used to deeply treat oilfield wastewater according to the application method of ceramsite filter material in Example 8.

[0082] The performance tests were performed on the ceramsite filter materials 1-7 prepared in the above Examples 1-7, the concrete test blocks prepared in Example 9, the clay ceramsite filter materials prepared in Comparative Example 1, and the concrete test blocks prepared in Comparative Example 3. The results are shown in Table 1 below:

[0083] Table 1 Basic properties of ceramsite filter material and its concrete test block

[0084]

[0085]

[0086] Standard: Test methods for cylinder pressure strength, bulk density, water absorption and porosity in GB / T 17431.2-2010 "Light aggregate and its test methods Part 2: Test methods for light aggregate" and CJ / T 299-2008 "Artificial ceramsite filter material for water treatment".

[0087] By comparing the above Table 1, it can be seen that the basic properties of the gasified slag unfired ceramsite of the present invention are equivalent to or even better than those of the traditional clay ceramsite, and both meet the cylinder pressure strength (≥8MPa) requirements of ceramsite filter materials.

[0088] In addition, the compressive strength of the concrete test block prepared by the present invention can reach up to 35.92MPa, which meets the requirements of C30 concrete and can be widely used in general building components; the strength of the remaining test blocks is also greater than C20, which is suitable for general residential foundations and non-high-strength load-bearing components. The compressive strength of the concrete test block prepared in Comparative Example 3 is 18.25MPa. According to the latest revised version of the "Concrete Structure Design Standard" GB / T50010-2010 of the Ministry of Housing and Urban-Rural Development, the concrete strength grade of the plain concrete structure should not be lower than C20, that is, the compressive strength of the plain concrete test block shall not be lower than 20MPa. It can be seen that the clay ceramsite with backwash failure cannot be used as aggregate to prepare concrete test blocks by adding cement.

[0089] The reason for this difference is that when unfired ceramsite is prepared using clay and cement, the main hydration reaction occurs to produce hydrated calcium silicate. However, hydrated calcium silicate has poor high temperature tolerance. When the temperature exceeds 400°C, hydrated calcium silicate will dehydrate and calcium hydroxide will decompose, resulting in a significant decrease in strength. In contrast, geopolymers formed by the reaction of aluminosilicates such as fumed slag and metakaolin with alkaline activators have higher heat resistance. In the low to medium temperature range of 300-500°C, they usually undergo slight mineral phase changes and removal of hydration water, but these changes generally do not lead to significant strength loss.

[0090] The ceramsite filter material prepared by the present invention has high hardness, is resistant to acids, alkalis and other chemical agents, can maintain stable shape and performance during backwashing, and avoids easy compaction like walnut shell filter material. Therefore, the ceramsite filter material is relatively convenient to clean and maintain during oilfield wastewater treatment, and the operating cost is relatively low.

[0091] After the unburned ceramsite filter materials of Examples 1-7, Comparative Examples 2 and Comparative Examples 4 were applied using the method of Example 8, the filtered water samples were taken every 1 hour to test the oil content. The test results are shown in Table 2 below:

[0092] Table 2 Comparison of the effects of ceramsite and walnut shell filter media on deep treatment of oilfield wastewater

[0093]

[0094] Standard: Q / SY DQ0605-2006 "Daqing Oilfield Reservoir Waterflooding Water Quality Indicators and Analysis Methods" stipulates that the oil concentration of wastewater after deep treatment is ≤5mg / L and the suspended solids concentration is ≤5mg / L, so the filtration end time is when the oil concentration of wastewater is greater than 5mg / L or the suspended solids concentration is greater than 5mg / L.

[0095] By comparing the above Table 2, it can be seen that the gasified slag unfired ceramsite of the present invention can achieve the sewage treatment effect of traditional clay ceramsite, and the treated sewage meets the sewage discharge and reinjection standards.

[0096] In summary, the present invention has achieved many technical innovations and breakthroughs by using coal gasification slag to prepare unfired ceramsite filter materials and applying them to the deep treatment of oilfield wastewater. First, the present invention effectively realizes the resource utilization of coal gasification slag and significantly improves its environmental value. Secondly, sodium silicate is used as an alkali activator and ceramsite is prepared using an unfired process, which greatly reduces carbon emissions and makes the preparation process more green, efficient, energy-saving and environmentally friendly. The strength range of the prepared unfired ceramsite is 8.33-23.28MPa, which fully meets the strength requirements of water treatment ceramsite (≥8MPa).

[0097] In addition, ceramsite filter media performs well in oilfield wastewater treatment, and its treatment effect is comparable to that of traditional clay ceramsite filter media and walnut shell filter media. The filter media can be recycled after backwashing. For ceramsite filter media that fail to backwash, the oil components can be removed by high-temperature roasting. The test results show that the strength of the ceramsite filter media after roasting varies little, and its strength range is 6.46-20.18MPa, which still meets the strength requirements of artificial lightweight aggregates (≥4MPa). In contrast, the strength of clay ceramsite drops significantly after high-temperature roasting, to only 3.32MPa, and its performance is obviously insufficient.

[0098] Finally, the present invention further explores the harmless treatment and reuse methods of waste filter materials. The calcined ceramsite filter material is added to cement as aggregate to prepare concrete test blocks. The test results show that the strength range of the ceramsite prepared by the present invention for concrete test blocks is 20.53-35.92MPa, which is higher than the C20 strength standard and is suitable for general residential foundations and non-high-strength load-bearing components. The strength of the concrete test block prepared from clay ceramsite is only 18.25MPa, which cannot meet the C20 strength requirement. In addition, because the waste walnut shell filter material has no recycling value, the processing process is complicated and the cost is high, it has obvious disadvantages in resource utilization.

[0099] The invention not only effectively solves the problem of processing waste filter materials, but also gives them new engineering application value, and is of great significance in resource utilization, environmental protection benefits and engineering applications.

[0100] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A coal gasification slag unburned ceramsite filter material, characterized in that: The invention comprises the following raw materials in parts by weight: 67.5-95 parts of coal gasification slag, 5-15 parts of active powder, 0-20 parts of metakaolin, 2-8 parts of expanded perlite, 0.1-0.5 parts of foam stabilizer, and 1-3 parts of foaming agent.

2. The coal gasification slag unburned ceramsite filter material according to claim 1, characterized in that: The coal gasification slag contains 95-98 wt % of ash, the particle size of the coal gasification slag is 0-0.25 mm, the particle size of the metakaolin is 0-0.25 mm, and the particle size of the expanded perlite is 0-0.074 mm.

3. The coal gasification slag unburned ceramsite filter material according to claim 1, characterized in that: The active powder comprises solid sodium silicate with a purity of 83.9%; the foam stabilizer is hexadecyltrimethylammonium bromide; and the foaming agent is hydrogen peroxide with a concentration of 30%.

4. A method for preparing the coal gasification slag unburned ceramsite filter material according to any one of claims 1 to 3, characterized in that: The steps include: S1. Mixing: weighing raw materials in parts by mass and mixing them evenly to obtain a mixture; S2, granulation: adding water and foaming agent to the mixture, mixing and placing in a granulator for granulation to obtain ceramsite raw material; S3, curing: subjecting the ceramsite raw material to aging treatment, steam curing and natural drying in sequence to obtain ceramsite filter material.

5. The method for preparing a coal gasification slag unburned ceramsite filter material according to claim 4, characterized in that: In step S1, before mixing, the raw materials are dried at 105° C.; during mixing, a planetary ball mill is used to run at a speed of 400 rpm for 5 minutes; in step S2, the granulator is a strong mixing granulator, the rotor speed of the granulator is 1400 rpm-1600 rpm, and the feed plate speed of the granulator is 30 rpm; the particle size of the ceramsite raw material is 2-3 mm.

6. The method for preparing a coal gasification slag unburned ceramsite filter material according to claim 4, characterized in that: In step S3, the aging temperature is 25±2°C; the aging time is 12-18h; the curing temperature is 40-80°C, the curing humidity is 95%, and the curing time is 6-15h; the natural drying temperature is 25±2°C, and the drying time is 12-18h.

7. An application of the coal gasification slag unburned ceramsite filter material as claimed in any one of claims 1 to 3, characterized in that: The ceramsite filter material is applied to the deep treatment of oilfield wastewater.

8. The use of the coal gasification slag unburned ceramsite filter material according to claim 7, characterized in that: The specific steps are as follows: The ceramsite filter material is loaded into the filter device, which is set up in a top-down flow manner and uses a metal mesh as a supporting layer; the oilfield wastewater enters the filter device from the top and is discharged from the bottom of the filter device after filtration.

9. The use of the coal gasification slag unburned ceramsite filter material according to claim 8, characterized in that: The diameter of the filter device is 30mm and the height is 1200mm; the oil content of oilfield wastewater is 15-50mg / L, and the solid suspended matter concentration of oilfield wastewater is 15-20mg / L; the filtration speed is 5m / h; concrete test blocks are prepared using ceramsite filter materials that have failed after deep treatment of oilfield wastewater.

10. The use of the coal gasification slag unburned ceramsite filter material according to claim 9, characterized in that: The specific steps for preparing concrete test blocks are as follows: The ceramsite filter material is calcined at a high temperature of 350°C-500°C for 1 hour, and then the calcined ceramsite filter material is mixed with cement to prepare a concrete test block, and standard curing is performed for 28 days to obtain a concrete test block; Among them, the mass ratio of cement: expanded clay filter material: water in the concrete test block is 1:4:0.5; the curing temperature is 20±2°C and the humidity is 95±2°C; the size of the concrete test block is 15cm×15cm×15cm.

Citation Information

Patent Citations

  • Sewage treatment material on basis of coal gasification fine residues and method for preparing sewage treatment material

    CN109734144A

  • Unfired ceramsite and preparation method thereof

    CN111548111A

  • Rapid concrete repairing material doped with fine coal gasification coarse slag, and preparation method and application thereof

    CN114315308A

  • Aerated concrete and preparation method thereof

    CN115849940A

  • Coal gasification slag unfired ceramsite and preparation method thereof

    CN117417175A

Cited By

  • Method and system for preparing combustible gas and light ceramsite by smoldering coal gasification slag and product

    CN121470989A